Polymicrobial biofilms related to dental implant diseases: unravelling the critical role of extracellular biofilm matrix. (4th May 2023) - Costa, Raphael C.; Bertolini, Martinna; Costa Oliveira, Barbara E.; Nagay, Bruna E.; Dini, Caroline; Benso, Bruna; Klein, Marlise I.; Barāo, Valentim A. R.; Souza, Joāo Gabriel S.
Abstract: Biofilms are complex tri-dimensional structures that encase microbial cells in an extracellular matrix comprising self-produced polymeric substances. The matrix rich in extracellular polymeric substance (EPS) contributes to the unique features of biofilm lifestyle and structure, enhancing microbial accretion, biofilm virulence, and antimicrobial resistance. The role of the EPS matrix of biofilms growing on biotic surfaces, especially dental surfaces, is largely unravelled. To date, there is a lack of a broad overview of existing literature concerning the relationship between the EPS matrix and the dental implant environment and its role in implant-related infections. Here, we discuss recent advances in the critical role of the EPS matrix on biofilm growth and virulence on the dental implant surface and its effect on the etiopathogenesis and progression of implant-related infections. Similar to other biofilms associated with human diseases/conditions, EPS-enriched biofilms on implant surfaces promote microbial accumulation, microbiological shift, cross-kingdom interaction, antimicrobial resistance, biofilm virulence, and, consequently, peri-implant tissue damage. But intriguingly, the protagonism of EPS role on implant-related infections and the development of matrix-target therapeutic strategies has been neglected. Finally, we highlight the need for more in-depth analyses of polymicrobial interactions within EPS matrix and EPS-targeting technologies' rationale for disrupting the complex biofilm microenvironment with more outstanding translation to implant applications in the near future.